Penerapan Pengembangan Sumber Daya Manusia Islami pada Unit Usaha Syariah - Tri Mulato (Cakrawala: Jurnal Studi Islam, 2018)
Shari'ah banking currently has a strong legal law with the presence of law number 21 of 2008 on shari'ah banking. It is very influential on the existence of sharia banking is increasingly in demand by many circles. Shariah banking continues driven in order to innovate in developing products to be able to reach a targeted market share of 5%. There are three types of sharia banking in Indonesia, namely Shariah Commercial Bank, Shariah Business Unit, and People's Bank of Sharia Financing. Of the three different types of Islamic banks are Shariah Business Unit itself, because not stand alone still follow the conventional bank, so much influence from the parent. Particularly related to the human resources of syariah banks, the syariah business unit is still in the shade of its parent, which is conventional bank, whereas both of them should be different. In this paper discussed about the implementation of Islamic human resource development in the Islamic business unit. The type of research conducted is a research or research by taking data from various sources that are then processed and drawn conclusions related to Islamic human resources. The results of this paper show / conclude there are some things related to the process of developing resources in Islamic banks are in line with the development of Islamic human resources. However, it is found that the application of Islamic human resources development has not been in line with the recruitment pattern of shariah business unit that has not been able to perform its own recruitment but still follow its conventional parent provisions. So that related to the criteria to be tb sharia bank has not been fulfilled.